Types of mathematical tasks used in secondary classroom instruction - Valbona Berisha; Ruzhdi Bytyqi (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study examined the quality and types of mathematical tasks used for classroom instruction in an upper secondary school – gymnasium. All the mathematical tasks presented in nine different school classrooms during the first semester of the school year 2018/2019 were analysed against a 5D analytical framework. The dimensions of the individual task analysis were contextual features; the answer forms required; forms of presentation; types of required mathematical activity and cognitive demands involved. Performed analysis gived perspective on the learning opportunities offered in classroom instruction for building mathematical competencies specified in the current state education curriculum. The results indicate that the selection of tasks was not in accordance with the curriculum requirements. Mostly, teachers used close-ended, non-applicative, lower-level cognitive tasks presented in symbolic form, promoting operations and calculations as a central activity. These types of tasks are usually associated with knowledge and skills of lower orders. In this case, classroom instruction had low potential and very little room left to build a significant portion of competencies and learning outcomes of higher orders.